HBR guide to beating burnout - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2021)
"Burnout is rampant. Recognize the signs and make the right changes now. The always-on workplace and increasing social pressures are leading to an unprecedented rate of burnout. Unmanaged, chronic work stress doesn't just lead to lower productivity and negative emotions--it can have dire personal and professional consequences. Are you and your team at risk? The HBR Guide to Beating Burnout provides practical tips and advice to help you and your team navigate the perils of workplace burnout and rediscover healthy engagement at work. You'll learn how to: recognize the risk factors, unravel the difference between being stressed and being burnt out, recognize the symptoms in yourself and others, understand how passion can lead to burnout, make the changes you need to make, now, return to productivity after burnout leads to apathy, help prevent burnout on your team, arm yourself with the advice you need to succeed on the job, with the most trusted brand in business"--
Section 1. Protecting yourself from burnout: Don't get surprised by burnout -- now the warning signs and take action / by Steven D'Souza -- Six causes of burnout, and how to avoid them -- consider which factors are the greatest risk for you / by Elizabeth Grace Saunders -- How to get through an extremely busy time at work -- what to do when working less isn't an option / by Alice Boyes -- How to avoid burnout while working from home -- the risk is high when work life and personal life blur / by Laura M. Giurge and Vanessa K. Bohns -- Making compassion a habit -- empathy has powerful stress-fighting powers / by Kandi Wiens and Annie McKee -- Collaboration without burnout -- ways to stay helpful while avoiding overload / by Rob Cross, Scott Taylor, and Deb Zehner -- Section 2. Bouncing back from burnout: Beating burnout -- steps you can take once you're aware of the symptoms / by Monique Valcour -- 5 steps for women to combat burnout -- they're at higher risk, and it's getting worse / by Ellen Keithline Byrne -- Even if you love your job, you may need to recharge -- it's not always burnout when you're exhausted by work / by Rebecca Knight -- To recover, regain your sense of control -- take positive action to break out of the victim mindset / by Elizabeth Grace Saunders -- Instead of pushing yourself too hard, help others around you perform -- shift from energized to energizing / by Merete Wedell-Wedellsborg -- Carve a new path at work -- designing your own role will lead to a more meaningful experience at work / by Jennifer Moss -- When burnout is a sign you should leave your job -- is it hurting your health, career prospects, or relationships? / by Monique Valcour -- Reawakening your passion for work -- five practical strategies to guide you / by Richard Boyatzis, Annie McKee, and Daniel Goleman -- Section 3. Preventing burnout on your team: Making work less stressful and more engaging for your employees -- foster wellbeing while improving business performance / b
Includes bibliographic references and index.
Description based on online resource; title from digital title page (viewed on February 09, 2021).
WorldCat record variable field(s) change: 650
Keywords: Burn out (Psychology); Leadership; Industrial management; Electronic books; Burn out (Psychology); Industrial management; Leadership; elektronické knihy; electronic books